Hopeoasis: A Donation Website for Empowering Sudanese Healthcare - Magdi, Mustafa; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2025)
Donation websites have become crucial tools for assisting those in need. This project presents HopeOasis, designed to meet Sudan’s critical healthcare needs amid ongoing civil conflict. The primary problem is the severe shortage of medical supplies, doctors, and access to medical treatment and consultations. HopeOasis aims to streamline healthcare donations, making essential medical resources and online medical consultations more accessible to affected communities. Developed using the waterfall methodology, the platform ensures a structured and reliable approach. Findings show significant improvements in medical supply distribution and increased donor participation. The platform’s transparency and user-friendly design build donor confidence and engagement. HopeOasis effectively centralizes donation efforts, enhances healthcare delivery, and ensures aid reaches the most needed areas, showcasing the potential for scalability and future feature integration.